Analisis Pengaruh CAR, NPF, FDR dan Inflasi terhadap Profitabilitas Perbankan Syariah di Indonesia - Misbahul Munir (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2019)
The increasing number of sharia financial institutions in Indonesia is accompanied by an increase in literature review regarding sharia financial institutions. Renewal of studies related to the development of Islamic finance in Indonesia is important to continue. This study aims to examine the factors that affect the level of profitability of Islamic banking in Indonesia in the latest conditions and the latest data. The approach used is quantitative descriptive. Based on the F test, the f-statistic value obtained was 0.000085 below 0.05 (five percent). In other words, the independent variables including CAR, NPF, FDR, and inflation simultaneously have a significant effect on the dependent variable ROA. Whereas in a formal manner, based on the t-test, the NPF variable has a positive and significant effect on ROA. While the CAR, FDR and inflation variables have no effect on ROA.